Incidence of Chlamydia trachomatis and Trichomonas Vaginalis Genital Infections among Non-Pregnant Women in Al - Najaf Province - Ohood Aqeed Radhi; Wijdan Dhaidan Shnain Al- Abbas (Kufa Journal for Nursing Sciences)
Background: Trichomonas vaginalis infections are greatly connected with the Existence of other STIs (gonorrhea, chlamydia, and Human Immunodeficiency Virus).